Relevance of Vedic Mathematics in Elementary Education (Bhartiya Knowledge Systems, 2024)
Vedic mathematicsis an ancient Indian mathematical system of education which includes mathematical calculation like addition, subtractions, multiplication, division, geometric algebraic, trigonometric problems. It is defined with 16 Vedic Sutras and 13 Sub Sutras with simple rules and concepts. The concepts of Vedic mathematics should be taught at the early stage of childhood as they can grasp the calculation easily in their mind. The New Education Policy, which intends to implement the Indian knowledge System in terms of education, defines the importance and practice of Vedic mathematics in early schooling. The idea of Vedic mathematics at an early stage can assist towards better development for students by improving the quality of computation which is already ingrained in our ancient knowledge.